Biofortification in Millets: A Sustainable Approach for Nutritional Security - Vinoth, A.; Ravindhran, R. (Frontiers in Plant Science, 2017)
Nutritional insecurity is a major threat to the worlds’ population that is highly dependent on cereals-based diet, deficient in micronutrients. Next to cereals, millets are the primary sources of energy in the semi-arid tropics and drought-prone regions of Asia and Africa. Millets are nutritionally superior as their grains contain high amount of proteins, essential amino acids, minerals and vitamins. Biofortification of staple crops is proved to be an economically feasible approach to combat micronutrient malnutrition. HarvestPlus group realized the importance of millet biofortification and released conventionally bred high iron pearl millet in India to tackle iron deficiency. Molecular basis of waxy starch has been identified in foxtail millet, proso millet and barnyard millet to facilitate their use in infant foods. With close genetic-relatedness to cereals, comparative genomics has helped in deciphering QTLs and genes linked to protein quality in finger millet. Recently, transgenic expression of zinc transporters resulted in the development of high grain zinc while transcriptomics revealed various calcium sensor genes involved in uptake, translocation and accumulation of calcium in finger millet. Biofortification in millets is still limited by the presence of antinutrients like phytic acid, polyphenols and tannins. RNA interference and genome editing tools (ZFNs, TALENs and CRISPR) needs to be employed to reduce these antinutrients. In this review paper, we discuss the strategies to accelerate biofortification in millets by summarizing the opportunities and challenges to increase the bioavailability of macro and micronutrients.